2008
DOI: 10.2319/090607-420.1
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Frictional Forces Generated by Three Different Ligation Methods

Abstract: Objective: To test the hypothesis that there is no difference between the frictional forces produced by a passive self-ligating bracket (SLB) in vitro and a conventional bracket (CB) used with two types of elastomeric ligatures. Materials and Method: The brackets, wires and ligation methods used in vitro were a passive SLB and a CB used with two types of elastomeric ligatures (conventional elastomeric ligature [CEL] and unconventional elastomeric ligatures [UEL]). The bracket ligation systems were tested with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
37
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 26 publications
8
37
0
8
Order By: Relevance
“…RS measured under these circumstances was due to experimental flaws due to incorrect alignment of the archwire within the bracket slot. [5][6][7][8] With the use of a stainless-steel chain almost all unwanted effects of malalignment, angulation, or torque between the bracket slot and the archwire were eliminated in the present study. The chain allowed the archwire to align itself perfectly within the bracket slot.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…RS measured under these circumstances was due to experimental flaws due to incorrect alignment of the archwire within the bracket slot. [5][6][7][8] With the use of a stainless-steel chain almost all unwanted effects of malalignment, angulation, or torque between the bracket slot and the archwire were eliminated in the present study. The chain allowed the archwire to align itself perfectly within the bracket slot.…”
Section: Discussionmentioning
confidence: 78%
“…[1][2][3][5][6][7][8][9][10] Many of the discrepancies in the results can be attributed to the different testing designs. Some authors used an experimental setup in which the archwire was pulled straight through the bracket slot without any angulation, torque, or force-moment applied.…”
Section: Discussionmentioning
confidence: 99%
“…4,11,12 The latest studies conducted with low-friction ligatures showed differences between the results of the friction produced by these elastomeric ligatures and conventional ligatures. 4,[11][12][13][14][15][16] Therefore, the aim of this study was to compare frictional resistance obtained by low-friction elastomeric ligatures and conventional ligatures in the presence of artificial saliva, and observe whether this variable changed after 21 days.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,12 Therefore, orthodontic forces must first overcome friction while the remaining force promotes bone remodeling, causing teeth to move. 1,5,7 Damon MX, Easy Clip, In-Ovation, Smart Clip self-ligating brackets, special Synergy brackets, and conventional Morelli brackets with 8-shaped ligatures are effective in eliminating ligation friction when the archwire is flat and undeflected. The purpose of this study was to investigate whether or not the different slot closing methods described above produce similar friction magnitudes when the archwire is subjected to deflection.…”
Section: Discussionmentioning
confidence: 99%
“…Self-ligating brackets, Slide unconventional elastomeric ligatures (Leone) and 8-shaped ligatures (Tecnident) as well as the special Synergy (Rocky Mountain) and Delta Force (Ortho Organizers) brackets are effective and equivalent options for the control of friction in the phase of dental leveling and alignment. 1,3,4,5 Archwire deflection-induced friction usually takes place in the initial phase of orthodontic treatment when the orthodontic slots are in different planes. Archwire deflection creates the forces responsible for correcting malpositioned teeth and simultaneously exerts pressure on anchorage teeth, generating deflection-induced friction, which undermines tooth movement effectiveness.…”
Section: Introductionmentioning
confidence: 99%